2017
DOI: 10.1080/15513815.2017.1281363
|View full text |Cite
|
Sign up to set email alerts
|

The Development of FVIII Inhibitors in Relation toIL10Gene Polymorphism in Hemophilia A Egyptian Pediatric Patients

Abstract: FVIII inhibitor formation in this group of Egyptian hemophiliacs was not correlated to IL10-1082A/G polymorphism, disease severity, or any of the treatment variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…One recent study from Egypt reported a 22% prevalence of FVIII inhibitors in patients with severe HA, 12 while another reported a prevalence of 12% in moderate to severe disease. 13 In turkey, a large recent study, including 657 patients with severe HA, found 15.8% to be positive for inhibitors. 14 Other reports also indicated an overall inhibitor prevalence of around 14% and a prevalence of 16.7% in patients with severe disease.…”
Section: Where Do We Stand?mentioning
confidence: 98%
See 1 more Smart Citation
“…One recent study from Egypt reported a 22% prevalence of FVIII inhibitors in patients with severe HA, 12 while another reported a prevalence of 12% in moderate to severe disease. 13 In turkey, a large recent study, including 657 patients with severe HA, found 15.8% to be positive for inhibitors. 14 Other reports also indicated an overall inhibitor prevalence of around 14% and a prevalence of 16.7% in patients with severe disease.…”
Section: Where Do We Stand?mentioning
confidence: 98%
“…Data from non‐Western countries are mainly based on cross‐sectional or retrospective studies. One recent study from Egypt reported a 22% prevalence of FVIII inhibitors in patients with severe HA, 12 while another reported a prevalence of 12% in moderate to severe disease 13 . In turkey, a large recent study, including 657 patients with severe HA, found 15.8% to be positive for inhibitors 14 .…”
Section: Where Do We Stand?mentioning
confidence: 99%